Das Selbstmordattentat im Bild: Aktualität und Geschichte von Märtyrerzeugnissen - Straub, Verena (transcript, 2021)
From martyr posts, to video testaments, to livestreams from the scene of the crime – a visual history perspective on a sensitive topic